Impact of microfinance on women's economic empowerment - Belay Mengstie (Journal of Innovation and Entrepreneurship, 2022)
Women's economic empowerment a strategy aimed at enabling women in decision-making, increment in income and asset ownership. The main aim of the study is to examine the impact of microfinance on women's economic empowerment. Data were derived from a questionnaire of a sample of 346 women clients of microfinance. Multiple regression and paired sampled t-test data analysis techniques were used in the study. Multiple linear regression result revealed that age, marital status, education level, credit amount, and number of training have significant effect on women's economic empowerment. However, previous business experience did not have significant impact on women's economic empowerment. Paired sampled t-test result revealed that there is significant mean difference before and after microfinance service in terms of income, asset, and saving. Microfinance has significant positive effect on women's economic empowerment by improving women's independent income, increasing asset possession levels, and improved monthly saving amount. Moreover, the study proved that microfinance has a positive impact on women's entrepreneurship development and business exposure.
Keywords: 650; Impact; Microfinance; Women economic empowerment